Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4081/jlimnol.2015.1216
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of Daphnia in a Northern Italy pond during the weather anomalous 2014

Abstract: This note reports a comparison between Daphnia phenology in the weather anomalous 2014 and a previous three years period (2011)(2012)(2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The presence of D. pulex in this area is important in the framework of conservation ecology. In fact, we have shown that it is the native European species instead of the invasive North American asexual clone (Rossi et al, 2015). Here we extend our research to 24 surrounding water bodies located in the Po river basin in the Cre-mona province that is one of the most productive areas of the Northern hemisphere (Bassanino et al, 2011).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The presence of D. pulex in this area is important in the framework of conservation ecology. In fact, we have shown that it is the native European species instead of the invasive North American asexual clone (Rossi et al, 2015). Here we extend our research to 24 surrounding water bodies located in the Po river basin in the Cre-mona province that is one of the most productive areas of the Northern hemisphere (Bassanino et al, 2011).…”
Section: Introductionmentioning
confidence: 64%
“…In the Po river Basin, we found a high genetic diversity within the D. longispina complex (five haplotypes with Pi 0.02077). Between 2011 and 2014, D. pulex dominated in the pond Pastore III while in 2015 it was partly replaced by D. longispina (Rossi et al, 2015;Rossi et al, in preparation). Due to high population fluctuation and spatial/temporal dispersal by resting eggs, D. longispina could have colonized the pond Pastore III from surrounding ponds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data recorded in 2014 and in 2015 were compared as, in the study area, mean temperatures in this 2-year period were very different. In 2014, the winter was much warmer while late spring and summer were much colder than the average recorded in the past and in 2015 [49]. In most of 2015, mean monthly temperatures were much warmer than the average recorded during the past.…”
Section: Introductionmentioning
confidence: 79%